UNMANNED AERIAL VEHICLE FOR AGRICULTURE AND DISASTER MANAGEMENT - Lakshmi, R.; Sunanthini, V.; Manohar, Gunaselvi; .Sudha, R; Stanley, Pearley (International Journal of Psychosocial Rehabilitation, 2019)
This paper represents the model of design, production and validation of a portable sensory program for crop management by sprinkling watering and disaster fields. The objective of this scheme includes an exceptional amount of toxic gas leakage detection and fire detection using sensors. Agriculture is essential in life and one of the diminishing fields. The farmers cannot stand in front of the huge markets. The cost of yield is increased while the ROI is more insufficient for the farmers. There are significant technologies have been developed to automate cultivation to reduce the production cost and to improve profits of the farmers. The study reveals that the importance of drone and the obligation to do more R&D of drone in crop growing . The sensors have been selected by taking into account of weather and plant development representation and the requirements for their business on board the quad rotor. The prime support of this term paper are the support of the quad rotor as a raised area for measuring ecological versatile and the resolving of the best possible locality of sensors on a quad rotor. And here we present the same quad rotor for the disaster field managing by using gas sensor for monitoring the poisonous gas was leaking or not and flame detection.